Mound builders & cliff dwellers - Time-Life Books (Alexandria, Va. : Time-Life Books, 1992)
Includes material on the Spiro Mound.
Contents: The Adena and the Hopewell : a monumental heritage (p.7) -- Essay: Stupendous piles of earth (p.33) -- Temple mound builders : the high and the mighty (p.43) -- Essay: Keys to the universe (p.69) -- The Southwest : thriving in a pitiless domain (p.79) -- Essay: The saga of "green table" (p.109) -- The Anasazi : masters of the canyons and cliffs (p.121) -- Essay: The wonders of Chaco (p.150) -- Timeline (p.160) -- Acknowledgments (p.162) -- Picture credits (p.162) -- Bibliography (p.164) -- Index (p.166).
Includes bibliographical references (p. 164-165) and index.
Keywords: Mound-builders.; Cliff-dwellers.; Indians of North America -- East (U.S.) -- Antiquities; Indians of North America -- Southwest, New -- Antiquities; East (U.S.) -- Antiquities; Southwest, New -- Antiquities; Indianen; Heuvels; Grotten; Cliff dwellers; East (U.S.) -- Antiquities; Indians of North America -- East (U.S.) -- Antiquities; Indians of North America -- Southwest, New -- Antiquities; Mound-builders; Southwest, New -- Antiquities